Possíveis destinos do carbono da serrapilheira no ecótono Cerrado-Pantanal - Martins, André Luiz (2017)
Considering the current situation in the world, where the concern with the anthropic greenhouse effect is determinant of the public policies of the development of the nations, the understanding of the natural processes that affect the biogeochemical carbon cycle is absolutely indispensable. As the phytophysiognomies of the Cerrado of Baixada Cuiabana show great variability in the accumulation of litter on the soil, this accumulation reveals and quantifies how much CO2 can be released in an eventual fire on the surface. Therefore, the transect of Campo Sujo produces a cumulative of carbon in average 1,3 Mg.ha1 .year -1 and can release around 5 Mg.ha-1 .year -1 of CO2. In this sense, the objective of the present work was to evaluate the dynamics of the production, accumulation and decomposition of the litter associated to its contribution with the organic matter of the soil and to the risk of burning it in an area of ecotone, area of Between the Cerrado-Pantanal. Five transects with distinct phytophysiognomies were analyzed: The Campo Sujo, the Cerrado Stricto Sensu, the Cambarazal, the Cerradão and a Cerrado Miscelanea. The litter produced in the transects evaluated presented a significant increase in the dry period, varying from 0,22 Mg.ha-1.month-1 in the Campo Sujo to 0,88 Mg.ha-1.month-1 in the Cerrado Stricto Sensu. Like wise, the accumulated litter presented a significant increase in the arid period, ranged from 5,74 Mg.ha -1.month-1 in the Campo Sujo to 14,42 Mg.ha-1.month-1 in Cambarazal. The estimated annual carbon production from litter ranged from 0,9 Mg.ha-1 .year -1 in the Campo Sujo and 4,3 Mg.ha1 .year -1 in the Cerrado Stricto Sensu. Like wise, the estimated annual nitrogen production from the litter varied from 0,02 Mg.ha-1 .year -1 in the Campo Sujo and 0,12 Mg.ha-1 .year -1 in Cerradão, confirming the hypothesis that in the Baixada Cuiabana accumulated litter contributes to the increased risk of fires. It was observed with the Monte Alegre Formula that over 86% of the evaluated days are between the medium, high and very high degrees of danger. The estimates of the Monte Alegre Formula in the region characterize the location with fire risk during 313 days of the year. Some situations in the transects evaluated favored the combustibility of the plant material deposited on the soil. High litter levels were observed on the soil, and fire probability indexes with high and extreme ranks were practically every month of the year. Likewise, the moisture content of litter accumulated on the soil presented values lower than Moisture content in plant material, and the on-site dryness index corroborates the understanding of increased combustibility in the dry season.